Superhydrophobic 3D‐Assembled Metallic Nanoparticles for Trace Chemical Enrichment in SERS Sensing (Small 51/2022). Issue 51 (22nd December 2022) - Liu, Youhai; Zhang, Nan; Tua, Dylan; Zhu, Yingkun; Rada, Jacob; Yang, Wenhong; Song, Haomin; Thompson, Alexis C.; Collins, R. Lorraine; Gan, Qiaoqiang
Abstract : Superhydrophobic 3D‐Assembled Metallic Nanoparticles In article number 2204234, Qiaoqiang Gan and co‐workers report a reproducible and sensitive surface‐enhanced Raman spectroscopy (SERS) chip that combines three‐dimensional‐assembled gold nanoparticles on superhydrophobic nanoporous substrates. This chip can simultaneously realize strong localized field and analyte enrichment. It demonstrates good reproducibility for fentanyl and heroin detection, paving the way towards quantitative sensing of abused drugs and other chemicals.